Modern Spain - Ávila López, Enrique (Understanding modern nations, 2015)
"Far from a usual reference book, Modern Spain takes the reader through the country's history, economy, and politics as well as topics that address Spain's popular culture, such as food, sports, and sexuality. Because of the interdisciplinary nature of its content, this book differs from the average typical English manuals that very rarely cover in depth the whole array of interesting issues that define Spain in the 21st century. The vast amount of information makes this book the perfect companion for any reader wishing to learn more about Spain. Packed with current facts and statistics, this book offers an unbiased view of a modern country, making it an ideal source for undergraduate students and scholars"--Publisher's website.